1996
DOI: 10.1159/000217189
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Pattern of Venous Thromboembolic Disease

Abstract: A review of 14,667 necropsy reports for every year from 1965 to 1990 and 6,436 diagnostic venograms performed from 1976 to 1990 was undertaken at a single teaching hospital. A progressive reduction in the percentage of necropsies reporting fatal pulmonary embolism from 6.1 to 2.1 %, occurred over the 25-year period (χ2 tests for linear trend with time p < 0.00001). Over the last decade, there has been a significant reduction in the rate of venographically diagnosed postoperative deep vein thrombosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 9 publications
1
51
1
1
Order By: Relevance
“…An autopsy study from Hong Kong documented a rising trend of PE from 1975 to 1989. 32,33 Conversely, the incidence of PE in autopsies reduced in the United States from 1966 to 1980, 34 and in the United Kingdom from 1965 to 2000, 35,36 but a Swedish study indicated that the incidence of PE was unchanged from 1957 to 1987. 37 These differences may be related to differences in clinically diagnostic accuracy, in population structure, in prophylaxis and management of DVT/PE, and in life style.…”
Section: Pe In Children Aged 0-9mentioning
confidence: 99%
“…An autopsy study from Hong Kong documented a rising trend of PE from 1975 to 1989. 32,33 Conversely, the incidence of PE in autopsies reduced in the United States from 1966 to 1980, 34 and in the United Kingdom from 1965 to 2000, 35,36 but a Swedish study indicated that the incidence of PE was unchanged from 1957 to 1987. 37 These differences may be related to differences in clinically diagnostic accuracy, in population structure, in prophylaxis and management of DVT/PE, and in life style.…”
Section: Pe In Children Aged 0-9mentioning
confidence: 99%
“…Recent registries and cohort studies suggest that ,10% of all patients with acute PE die within the first 3 months after diagnosis [3,4]. Of all patients admitted to hospitals, 1% die of acute PE and 10% of all in-hospital deaths are PE-related [2,5,6]. Taken together, these data demonstrate that VTE is a potentially life-threatening disease.…”
mentioning
confidence: 94%
“…In addition acute and chronic illness increases the patient's predisposition to occurrence of thrombosis [4,5]. About 70-80% of fatal pulmonary embolism (PE) cases in the hospital occur in medical (non-surgical) patients [6][7][8]. Therefore patient's DVT risk assessment is necessary in deciding to start thrombosis prophylaxis interventions.…”
Section: Introductionmentioning
confidence: 99%